University Ranking and Information Disclosure: The Case of Indonesia - Sri Pujiningsih; Helianti Utami (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to explore the information disclosure level of universities in Indonesia and its relationship with university ranking. Data were collected from universities’ reportspublished in their website from 2018 to 2020 (53 Observations). Using content analysis and regression tests, this study found a low level of information disclosure in universities in Indonesia. The disclosure of sustainability aspect is the lowliest level (9%) compared to the other information disclosures. The intellectual capital disclosure is not explicitly stated in the universities’ reports. The results of the regression test confirmed that the universities’ ranking have a positive effect on the universities’ disclosure level. The study supports the applicability of the signal theory in the context of higher education institutions.